Generalized Anxiety Disorder and Its Relationship with Dental Anxiety among Pregnant Women in Dammam, Saudi Arabia. (22nd February 2022) - Nazir, Muhammad Ashraf; AlSharief, Mishali; Al-Ansari, Asim; El Akel, Ahmed; AlBishi, Fai; Khan, Shahd; Alotaibi, Gadah; AlRatroot, Soha
Abstract : Objective . To assess the relationship between generalized anxiety disorder (GAD), dental anxiety (DA), and other factors among pregnant women. Methods . The Generalized Anxiety Disorder (GAD-7) scale and the Modified Dental Anxiety Scale (MDAS) were used to evaluate GAD and DA, respectively. Hard copies of self-administered questionnaires were distributed among 780 pregnant women attending hospitals/health centers in Dammam, Saudi Arabia. Results . About 31.7% of the participants demonstrated minimal anxiety, 37.9% mild anxiety, 19.7% moderate anxiety, and 10.6% severe anxiety. The mean GAD score of the sample was 7.53 ± 5.16 which differed significantly among women in the first (7.74 ± 5.47), second (6.82 ± 4.64), and third trimesters (8.13 ± 5.37) P = 0.029 . Pregnant women who performed routine dental visits demonstrated lower GAD (6.98 ± 5.23) than those who visited dentists for consultation, pain, or treatment (7.58 ± 5.07). The mean GAD score was significantly higher among participants with dental pain or discomfort during the last 12 months (8.12 ± 5.05) than among those without pain or discomfort (7.02 ± 5.2) (P 0.003). Similarly, the participants with DA showed a significantly higher mean GAD score (7.69 ± 5.17) than those without DA (5.93 ± 4.71) (P 0.006). Multivariate linear regression showed that GAD significantly correlated with DA ( B = 0.225, P < 0.001 ). Conclusion . In the present study, GAD was common among pregnant women which significantly correlated with DA. Pregnant women with DA and dental pain demonstrated high GAD. Preventive and therapeutic measures should be taken to reduce GAD and DA during pregnancy.